Prosedur Penagihan Piutang pada Anugrah Jaya Motor Surabaya - Salma Maria Regina Mano; Tjandra Wasesa (Jurnal Pengabdian Masyarakat, 2024)
Economic development in Indonesia is currently very rapid. This is directed by the number of companies that grow every year. The development of this company is inseparable from business competition in achieving profits, capturing market share and consumer attention. The ability to seize from competitors is inseparable from the company's marketing strategy. A company's marketing includes promotional efforts and sales strategies, both cash and credit. Companies currently generally sell more of their products on credit because this sales system is chosen as one of the improvements to the form of sales that is suitable at this time. The purpose of providing credit from the customer's side is to provide convenience and flexibility for customers in making payments. This is what CV. Anugrah Jaya Motor Surabaya does. As one of the motorcycle spare part product distributor companies. CV. Anugrah Jaya Motor Surabaya also provides convenience in terms of selling goods to customers. To attract customers and provide convenience in making payments. CV. Anugrah Jaya Motor Surabaya not only provides cash sales but also credit sales as an alternative if consumers or customers do not have cash when purchasing goods. However, the convenience of credit sales does not make all customers consistent in making payments on time. There are customers who cannot fulfill their obligations in making credit payments on time.